Islamic Index Dengan Pendekatan Ekonomi Islam Terhadap Pengaruh Strategi Judgment Dalam Konsep modal kerja dan Pendapatan Pada Masa Pandemi Covid 19 (Studi Kasus : Usaha Ekonomi Rakyat Di Kota Medan) - Lubis, Arnida Wahyuni; Lestari Nasution, Annio Indah (ITB AAS INDONESIA Surakarta, 2023)
The COVID-19 pandemic has greatly affected all business sectors. Where the Islamic index data illustrates a graph that is very influential on the ups and downs of economic growth at this time. The Islamic economic approach moves human behavior as social beings who have human relationships with their bonds, the Government is very worried about a spike in dynamics that will affect the capital and income of economic actors globally. This impact is felt on the people's economic business, especially in the city of Medan. The number of people's economic efforts in the city of Medan involving various sectors of food, clothing and services. The purpose of this study was to determine the working capital of the people's economic business during the covid 19 pandemic, to find out the people's economic business income was measured by the judgment strategy during the covid 19 pandemic, and to find out the economic growth of the people's economic business was measured by the Islamic index during the covid 19 pandemic. . The method used in this research is a qualitative and quantitative approach to peer analysis content. This type of paper is using qualitative and quantitative data or mixed methods by collecting secondary data, namely articles, research results, and reference books published in the last 5 years. It will be described by analysis and using data testing methods. From the data available, it is clear that the people's economic business has decreased both in terms of the number of existing business sectors and also in income, this has an impact from the covid 19 pandemic. . The low level of human resources owned by the community and the conditions of the COVID-19 pandemic have resulted in the community being unable to meet their daily needs and many business sectors have suffered losses. One other factor is the low purchasing power of the people. With the occurrence of the phenomenon because there are still capital, human resources, business sector finance, government policies that are not yet optimal. The steps taken to overcome this are the factor of strengthening capital in Islamic financial institutions, socialist judgment strategies, and the country's economic growth Keywords: Islamic Index, Judgment Strategy, Working Capital Concept, Income, Covid 19 Pandemic